MEDIA PEMBELAJARAN BERBASIS APLIKASI ANDROID DENGAN PENDEKATAN INKUIRI TERBIMBING PADA MATERI MEDAN MAGNET DI KELAS XII SMA - Wardani, Sintia Febry; M. Rahmad, M. Rahmad; Irianti, Mitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The rapid use of technology in individuals learning in school has an impact inthe field of education to involve technology in the learning process, both in methods andlearning media. The emergency period that occurred in the world in 2019 causedthelearning process to be carried out from home or commonly called online, so it wasnecessary to develop android application-based learning media with a guided inquiryapproach in delivering learning materials. The purposeof this research is to developlearning media and to test the validity of the android application-based learning media.The development of this learning media is expected to be able to provide benefits tostudents so that students are motivated to learn magnetic field material independently,as well as assist in achieving learning goals online and offline. The developmentresearch model used in this research is the ADDIE model (Analyze, Design,Development, Implementation, and Evaluation). In determining the level of mediavalidity, this research used a validation sheet filled out by three validators, as well asan analytical questionnaire filled out by teachers and students. The results of thevalidation by the three validators stated that the android application-based learningmedia was valid in the level of validity with an average final score of 3.3, and thecriteria were very good. Based on the results of the validation of the learning media, itis said to be suitable for use in learning activities.Keywords: Learning Media, Android Applications, Guided Inquiry, Magnetic Field.